Tuning Medical Foundation Models for Inner Ear Temporal CT Analysis with Plug-and-play Domain Knowledge Aggregator - Wan, Weixun; Jiang, Xinyang; Wang, Zilong; Li, Bei; Zhao, Cairong (AAAI Conference on Artificial Intelligence, 2026)
High-resolution computed tomography (CT) is essential for diagnosing hearing loss and planning interventions such as cochlear implantation, as it provides detailed visualization of inner-ear anatomy. This paper focuses on advancing AI-based analysis of inner-ear CT scans to support clinical decision-making. However, a major challenge lies in the scarcity of annotated data, which limits the applicability of conventional supervised learning techniques. To address this, we present the first publicly available Children's Inner Ear CT Dataset (CIED), comprising 722 CT scans labeled for structural anomaly detection, postoperative hearing outcome prediction, and anatomical segmentation. In addition, we explore the use of medical foundation models to improve generalization in data-scarce scenarios. Existing parameter-efficient adaptation methods often fall short in two ways: they lack a unified mechanism to adapt across diverse foundation model architectures and they are not specifically designed to incorporate domain expert knowledge of inner-ear anatomy and pathology. To overcome these limitations, we propose Domain Knowledge Guided Tuning (DKGT), a plug-and-play framework that introduces a unified adapter—Domain Knowledge Aggregator (DKA)—to inject radiomics-based anatomical features into foundation models via cross-attention. DKA supports various backbone types and preserves pretrained representations of foundation model while enabling multi-layer integration of expert knowledge. Extensive experiments across multiple tasks demonstrate that DKGT consistently outperforms state-of-the-art classification methods, achieving superior performance and generalizability on inner-ear CT analysis.